Numerical investigation of the natural convective heat loss of a solar central cavity receiver with air curtain. (April 2019) - Fang, Jiabin; Tu, Nan; Torres, Juan F.; Wei, Jinjia; Pye, John. D.
Highlights: The effects of air curtain on the natural convection of cavity receivers were numerically analyzed. The variation trend of heat loss with the inclination angle of air nozzle was investigated. The variation trend of heat loss with the outlet velocity of air nozzle was studied. The heat loss reduction effects of air curtains with different widths and temperature were compared. Abstract: Central receiver in a solar tower power system absorbs the solar energy and transfers heat to the working fluid. It is of great importance to reduce the heat losses of the receiver. In the present work, a plane air nozzle was installed on top of a solar cavity receiver in order to create an air curtain. The effects of air curtain on the natural convection of the cavity receiver were numerically analyzed. Four parameters of the air nozzle, including the inclination ( θnoz ), the width ( Lnoz ), the outlet temperature ( To, noz ) and the outlet velocity ( uo, noz ), were considered as the factors. The results indicate that the air curtain could effectively prevent the hot air from flowing out of the cavity. It can enlarge the stagnation zone inside the cavity and suppress the natural convection on the internal surfaces. The convective heat loss monotonically decreases with increasing θnoz . The downward facing ( θnoz  = 90°) air nozzle produced the highest drop in the convective heat loss. A reduction of 28.6% can be achieved when a downward facing nozzle with 600 mm in width is used. The optimal uo, noz decreases with increasing Lnoz .